Isolation of Thymol from Trachyspermum ammi Fruits for Treatment of Diabetes and Diabetic Neuropathy in STZ-Induced Rats - Neetu Sachan (BioMed Research International, 2022)
Terpenoids and phenols from Trachyspermum ammi (T. ammi) have reported some pharmacological actions. The objective of the work was to isolate the active constituent, its identification by spectroscopic techniques, and evaluation of the antidiabetic and neuroprotective activity from T. ammi on STZ Wistar rats. The dried fruits of T ammi were kept in a hydrodistillation apparatus to collect essential oil. The isolated fraction went through TLC, UV, FTIR, HPLC, HRMS, C13, and 1H NMR for characterization. Two dosage concentrations from the isolated compound were prepared as 10 and 20 mg/kg for treatment groups. The groups were tested for thermal and mechanical hyperalgesia, writhing, grip strength, spontaneous locomotor test, neuromuscular coordination tests, and histopathological and lipid profile analysis. Diabetes was induced by streptozotocin (45 mg/kg i.p.) and 12 weeks of treatment-induced diabetic neuropathy in Wistar rats. Biomarkers were evaluated to understand the neuropathic protection of thymol on STZ-treated Wistar rats. The biomarker studies (SOD, NO, LPO, Na+K+ATPase, and TNF-α) further confirmed thymol’s diabetic neuropathy protective action. This study suggests that isolated compound thymol was antidiabetic and neuroprotective as it has shown controlled glucose levels defensive nerve damage in STZ Wistar rats. P<0.05 level of significance was observed in the levels of endogenous biomarkers, fasting blood glucose levels, actophotometer response, and response latency in treated groups compared to the diabetic group, whereas P<0.001 level of significance during lipid profile levels, thermal algesia, and neuromuscular comparison tests was noted in treated groups compared to the diabetic group.